Penerapan Multimedia Pembelajaran Interaktif Berbasis PowerPoint untuk Meningkatkan Hasil Belajar pada Teknik Dasar Pengelasan SMAW di SMK IPT Karangpanas Kota Semarang - Bahrun Samudra; Muhammad Khumaedi; Kriswanto Kriswanto (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the effectiveness of interactive learning multimedia based on PowerPoint in improving students’ learning outcomes in the subject of Basic SMAW Welding Techniques at SMK IPT Karangpanas, Semarang City. The study employed a quantitative approach using a quasi-experimental design with a nonequivalent control group design type. The participants consisted of 60 tenth-grade students majoring in welding engineering, divided into two groups: an experimental group taught using interactive PowerPoint multimedia and a control group taught through conventional methods. Learning achievement data were collected using validated and reliable pretest and posttest instruments. Data were analyzed using t-tests and Normalized Gain (N-Gain) analysis. The results revealed a significant difference between the experimental and control groups, with mean posttest scores of 80.67 and 70.53, respectively (p < 0.001). The experimental group achieved an N-Gain value of 0.5639 (high category), while the control group achieved 0.3475 (moderate category). These findings indicate that interactive learning multimedia based on PowerPoint effectively enhances students’ learning outcomes. The media proved to be a practical, low-cost, and engaging alternative that bridges the limitations of conventional learning and supports vocational education improvement.